Brassinolide improves nutrient value in storage roots of Raphnus sativus L. var Pusa chetki long - Vidya Vardhini, B; Sujatha, E; Seeta Ram Rao, S (Recent Research in Science and Technology, 2015)
The effect of brassinolide on the qualitative changes in the storage roots of radish was studied. Brassinolide stimulated the growth of radish roots. The root growth promotion was associated with increased levels of reducing sugars, starch, soluble proteins and minerals like phosphorous, potassium, calcium, iron and sodium. Brassinolide further increased the contents of ascorbic acid and niacin present in the roots indicating their ability to improve the over all quality of storage roots of radish.